Fostering Critical Thinking Through PBL in Students of 9th Grade at Institución Educativa San José in Itagüí, Colombia (2018)
ABSTRACT: This action research aims to explore how the implementation of Problem-based Learning (PBL) fosters ninth grade students critical thinking at Institución Educativa San Jose in Itagüí, Colombia. All the emergent information was gathered through a journal, a survey, an interview and students work. The findings evidenced that PBL not only fosters students critical thinking and empowerment, but also it develops attitudes, values and language skills in students.